Synthesis of non‐agglomerating submicron/nano‐Yb2Si2O7 powders by a carbon‐coated coprecipitation method. Issue 9 (4th May 2022) - Liu, Jingting; Luo, Zhixin; Yang, Jinxing; Oh, Yoonsuk; Wu, Zhen; Sun, Luchao; Wang, Jingyang
Abstract: We herein report a novel carbon‐coated coprecipitation method to synthesize non‐agglomerating submicron/nano‐β‐Yb2 Si2 O7 powders. Yb(C2 H3 O2 )3 ·4H2 O and silica sol (alkaline) were chosen as the ytterbium source and silicon source, respectively. A carbon surface layer is processed using sucrose as carbon source to hinder the contact and sintering of β‐Yb2 Si2 O7 particles during heat treatment under a protective atmosphere, and then the carbon layer could be completely removed by inletting air at 900°C during cooling process. The as‐synthesized Yb2 Si2 O7 powders demonstrate an average size of 271 nm with a narrow distribution of 142–531 nm. The results show that the carbon layer could successfully solve the severe agglomeration or sintering of nanometer β‐Yb2 Si2 O7 particles during the calcination process. The as‐developed carbon‐coated coprecipitation technique is an effective method to fabricate high purity submicron/nano‐Yb2 Si2 O7 powders.